COMPOSITION AND TECHNOLOGY OF PREPARATION OF NUTRIENT MEDIUM FOR REPRODUCTION OF POTATO PLANTS IN VITRO (Scientific journal of the Fergana State University, 2025)
The article describes the technology of nutrient media preparation for microclonal propagation of potato plants in vitro. The importance of nutrient media in the reproduction of potato plants under “in vitro” conditions, and the means of accelerating the dynamics of growth in the development of plants have been studied. Information on different ratios of MS nutrient medium, vitamins and auxin, cytokinin in different concentrations for the development of potato plants is given.